Drowning - Sarvesvaran, R. (College of Pathologists, Academy of Medicine Malaysia, 1992)
A body recovered from the water does not necessarily imply that death was due to drowning. The diagnosis of drowning is discussed together with the significance of the "diatom" and biochemical tests.